Moscas sarcofágidas de Costa Rica (Diptera; Cyclorrhapha) - Jirón Porras, Luis Fernando (1982)
A brief review of the sarcophagid flies of Costa Rica revealed the presence of 34 species in 21 genera. Some of these species are associated with flowers, rotting fruits and human cadavers.